Effects of inner angle of bowl, flow rate and speed on the efficiency of glycerol separation from the raw biodiesel using cylindrical bowl centrifuge - Chungcharoen, Thatchapol; Netjaibun, Kanokphan; Pratabkong, Thaweesak; Suwannasam, Puttapong; Limmun, Warunee (My University, 2017)
The centrifugal technique has been widely used for separation of fluids with moderately high viscosities because it provides an efficient separation in short residence times. In this work, the cylindrical bowl centrifuge was selected for separation of raw biodiesel and glycerol. In addition, the inner angle of bowl, flow rate and speed were investigated on their effects on the efficiency of separation. The experimental results showed that the inner angle of bowl and the flow rate affected the efficiency of separation significantly. The increase of inner angle of bowl (from 90 to 135 degree) and flow rate (from 50 to 200 ml/min) provided the increase of separation efficiency. In term of speed, the efficiency of separation was increased when increasing the speed from 1,800 rpm to 2,100 rpm. On the other hand, the efficiency of separation was decreased when increasing the speed from 2,100 rpm to 2,400 rpm. The efficiency of cylindrical bowl centrifuge was in the ranges of 29.17-39.83%, 52.83-61.83% and 84.6-91.4% for bowl inner angles of 90, 120 and 135 degree, respectively. The bowl inner angles of 135 degree, flow rate of 200 ml/min and speed of 2,100 rpm were appropriate conditions for glycerol separation from the raw biodiesel using cylindrical bowl centrifuge.
Keywords: Centrifuge; Efficiency; Raw biodiesel; Separation